Perilaku Memilih Kelompok Disabilitas Sensorik dalam Pemilihan Presiden dan Wakil Presiden Tahun 2024 di Kota Binjai - Mutiara Azzahra Lubis; Prayetno Prayetno (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
This research aims to find out how the voting behavior of groups of people with sensory disabilities is and what factors influence the political choices of groups of people with sensory disabilities in the 2024 Presidential and Vice Presidential elections in Binjai City. The method used in this research is quantitative descriptive. In order to answer this problem, researchers used data collection techniques in the form of questionnaires and documentation. The population in this study was 213 people, and the sample was 68 people who were calculated using the Slovin calculation technique. The data obtained was then analyzed using the formula P = f/n x 100%. he results obtained from this research are that the group of voters with sensory disabilities who participated in voting in the 2024 Presidential and Vice Presidential elections tended to be rational voters, namely 75.32% voted based on the Vision and Mission, Programs and Track Record of the Presidential and Vice Presidential candidates. 2024 . Critical voters, namely 17.95%, chose based on social background, educational background, and the political party carrying the 2024 presidential and vice presidential candidates. Traditional voters, namely 5.45%, chose based on closeness to certain religious figures or religious leaders, and Skeptical voters, namely 1.28%, voted based on issues and offers of assistance from the 2024 Presidential and Vice Presidential candidates. Based on this description, overall voters with sensory disabilities in Binjai City in 2024 are rational voters. The factors that influence the political choices of voters with disabilities in Binjai City in the 2024 Presidential and Vice Presidential elections are classified into two factors, namely internal factors from the voter and external factors from the organizing committee and the social environment in the 2024 elections.